Whirling into the World: The Duality of Dance Hostesses' Labor and Social Praxis in Postwar Singapore - Yao, Kuo Mei (Tanjong Malim, 2023)
Whirling into the World: The Duality of Dance Hostesses' Labor and Social Praxis in Postwar Singapore by Yao, Kuo Mei